Perhitungan Waktu Ijtimak Awal Bulan Hijriyah Dengan Aplikasi Microsoft Excel Memanfaatkan Algoritma Jean Meeus - Handhita, Emye Tegar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Muslims have several religious rituals that are being done on certain dates such as the fasting of Ramadan, Eid al-Fitr and the Hajj pilgrimage. These religious rituals are closely related to the Hijri calendar system. The Hijri calendar system is based on the period of Moon's revolution around the Earth. Meanwhile, there are two methods for determining the beginning of the Hijri month, they are Imkanu Rukyat and Wujudul Hilal. Unlike Imkanu Rukyat which requires observation of the Hilal, Wujudul Hilal determines the beginning of the Hijri month entirely based on mathematical calculations. One of important variable in determining the beginning of the Hijri month is the Ijtimak time, which is the time when the Sun overtake the Moon from behind. One of calculation method that can be used to calculate the Ijtimak time is Jean Meeus Algorithm. The Jean Meeus Algorithm has many calculation steps and several complex formulas. To help us doing this calculation, we can use Microsoft Excel application. To find out the accuracy level of the Ijtimak time that has been calculated, it is then compared with the data from NASA's SKYCAL site.